2000
DOI: 10.18388/abp.2000_3984
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amphiphilic compounds on membranes.

Abstract: On the basis of Gortel & Grendel (J. Exp. Med., 1925, 41, 439-494) discovery, the importance of the lipid bilayer as an integral and indispensible component of the cell membrane is discussed. In particular, attention focuses on the interaction between membranes and amphiphilic substances. The effect on membranes of quaternary ammonium salts, both in the form of pesticides and oxidants as well as organic compounds of tin and lead are discussed in greater detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 29 publications
(19 reference statements)
0
38
0
Order By: Relevance
“…For example, DABCO derivatives containing one long alkyl chain were active against Gram‐positive and Gram‐negative bacteria as well as fungi 30, 31. When attached to insoluble carbohydrate and protein‐based materials, they also showed very high antimicrobial activities 31–33. However, the activity of the DABCO group depends on the length of the alkyl chain attached to it, and an increase in alkyl chain length was shown to increase the antimicrobial activity 30, 33.…”
Section: Introductionmentioning
confidence: 99%
“…For example, DABCO derivatives containing one long alkyl chain were active against Gram‐positive and Gram‐negative bacteria as well as fungi 30, 31. When attached to insoluble carbohydrate and protein‐based materials, they also showed very high antimicrobial activities 31–33. However, the activity of the DABCO group depends on the length of the alkyl chain attached to it, and an increase in alkyl chain length was shown to increase the antimicrobial activity 30, 33.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic chain length between 12 and 18 carbons processed an excellent antimicrobial activity. 33,34 DMAE-CB has a long lipophilic chain with 16 carbons according to the previous studies, 17 but chain length of DMAEMA-PMDPM salt is very short, so this might be the reason why DMAEMA-PMDPM salt has a higher MIC/ MBC. The anionic part of QSA monomer could affect the bactericidal activity but the law is not very clear now.…”
Section: Discussionmentioning
confidence: 92%
“…The activity depends both on the character of the polar heads (size, electric charge distribution) and hydrocarbon chains (length, saturation, multiple chains). 33 The results showed that the antimicrobial property of the new monomer is lower than DMAE-CB, especially for C. albicans. There may be some reasons for this phenomenon.…”
Section: Discussionmentioning
confidence: 93%
“…[41] Since the F O rotor of F 1 F O complex is embedded in the inner membrane, any change in the bilayer properties can modulate the catalytic activity and also affect its sensitivity to inhibitors. [42] Butyltins are amphiphilic [43] and their butyl arms facilitate their incorporation within phospholipid acyl chains ( Fig. 1).…”
Section: Effects Of Butyltin (Iv) N+ Compounds On Membrane Bilayer Prmentioning
confidence: 99%
“…[25][26][27] Any decrease in the negative charges (or increase in positive charges) on the membrane surface decreases the accessibility of organotins for electrostatic reasons and conversely an increase of negative charges (and decrease of positive charges) favours their incorporation. [43,44] Accordingly, electrostatic interactions could also explain synergistic or antagonist effects of other co-present xenobiotics, including butyltin derivatives. [45] In model systems, butyltins are incorporated into phospholipids such as phosphatidylcholine, phosphatidylethanolamine and phosphatidylserine, where they perturb the thermotropic and structural properties.…”
Section: Effects Of Butyltin (Iv) N+ Compounds On Membrane Bilayer Prmentioning
confidence: 99%